“Nivel de conocimiento sobre bioseguridad frente a la COVID-19 en alumnos de Estomatología, UNT 2021” - Quiroz Cabanillas, Lucy Rosmery (2022)
Level of Knowledge on Biosafety against COVID-19 in Stomatology Students, UNT 2021"Objective: To determine the level of knowledge about biosafety against COVID-19 in Stomatology students, UNT 2021. Methodology: This research study is basic, descriptive, cross-sectional and free regimen.Material and method: The sample consisted of a total of 98 third, fourth, fifth and sixth students from the UNT Faculty of Stomatology enrolled in the 2021 academic year; 63 belong to the female gender (64.3%) and 35 belong to the male gender (35.7%); of which 25 students belong to the third year (25.51%), 13 students belong to the fourth year (13.27%), 25 students belong to the fifth year (25.51%) and 35 students belong to the sixth year (35.71%). They were evaluated using the previously validated questionnaire-type survey instrument.Results: The level of Knowledge about Biosafety against COVID-19 in Stomatology students of the UNT, 2021, from third to sixth year was: 6.1% with "Low" level, 87.8% with "Medium" level and 6.1% with “high” level Conclusions: Stomatology students of the National University of Trujillo in the academic year 2021, have a predominantly "Medium" (87.8%) level of knowledge about Biosafety against COVID-19.